Ternstroemia kobuskii (Pentaphylacaceae), a new canopy tree species to the Brazilian Atlantic Rainforest - Vieira, Jaqueline Alves [UNESP] (2024)
Here, we describe a new species of Ternstroemia (Pentaphylacaceae) from the Brazilian Atlantic Rainforest. Ternstroemia kobuskii differs from other extra-Amazonian species of Ternstroemia due to its height, reaching up to 28 meters, corresponding to a canopy tree, and its fruit, which is circumscissile-dehiscent, 3-locular, with 1–2 seeds per locule. Ternstroemia kobuski populations are limited to few specimens and a small number of localities in high-altitude slope forests, such as Santa Teresa (state of Espírito Santo) and Tabuleiro Forests, such as Una, and Belmonte (state of Bahia).